STRATEGI PENINGKATAN DAYA SAING LADA PUTIH INDONESIA MELALUI ANALISIS PENAWARAN EKSPOR DAN PERMINTAAN IMPOR LADA PUTIH DUNIA - EDIZAL - (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2007)
This study is competitive increasing strategy of Indonesian white pepper (muntok whitepepper). The main objective of this study are : 1) The analysis supply for export whitepepper from Indonesia, Malaysia, Brazil and Singapore; 2) The analysis demand for importwhite pepper by United State of America, European Economy Community, Japan, Singaporeand ROW. The results of supply export white pepper from Indonesia, Malaysia, Brazil andSingapore in the short run is inelastic. In the long run supply export white pepper fromIndonesia, Malaysia, and Brazil is elastic, meanwhile Singapore is inelastic. The result ofdemand for import white pepper by United State of America, European EconomyCommunity, and Japan an ROW in the short run is inelastic, meanwhile Singapore is elastic.